2019
DOI: 10.1186/s12916-019-1361-2
|View full text |Cite
|
Sign up to set email alerts
|

DIABRISK-SL trial: further consideration of age and impact of imputations

Abstract: Type 2 diabetes mellitus (T2DM) is a major cause of morbidity and mortality worldwide. Early interventions may help to delay or prevent onset of cardiometabolic endpoints of clinical importance to T2DM patients. Wijesuriya et al. ( BMC Med 15:146, 2017) published results of a randomised controlled trial in Sri Lanka testing the effect of two lifestyle modification programmes of varying intensity in participants aged 5–40 years with risk factors for T2DM. The intervention measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We appreciate the interest that Gkioni et al [2] have shown in our published study by highlighting the importance of age differentiation, retention and missing data as factors that need to be considered to understand the full potential of the benefits observed in our study. We have outlined below the detailed response to each of these factors and the results of further analyses are also reported.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…We appreciate the interest that Gkioni et al [2] have shown in our published study by highlighting the importance of age differentiation, retention and missing data as factors that need to be considered to understand the full potential of the benefits observed in our study. We have outlined below the detailed response to each of these factors and the results of further analyses are also reported.…”
Section: Introductionmentioning
confidence: 74%
“…Gkioni et al [2] highlight the importance of further subcategory age differentiation as a factor to consider when interpreting the results of the intervention. As detailed in our original publication [1], the results for those below the age of 18 were post hoc and thus exploratory, and establish the platform and rationale for further studies in this population.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations